Important Role of Civic Education in Multi-Ethnic Countries Malaysia and Singapore - Sari, Serli Retno (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2018)
This article discusses about the role of citizenship education in multi-ethnic countries, namely in Malaysia and Singapore. Malaysia and Singapore are two former British colonies, and in the population, there are three main ethnic groups namely China, Malay and India. This article is study of literature by using the comparative method by analyzing 14 national and international journals related to citizenship and diversity education in Malaysia and Singapore. Based on the results of this research, there is a difference in the management of ethnic diversity in Malaysia and Singapore. However, both in Malaysia and Singapore, citizenship education equally play an important role in creating a harmonious society even in the diversity of cultures, languages, religions and customs. Keywords: citizenship education, multi-ethnic, multicultural, Malaysia, Singapura Abstrak Artikel ini membahas tentang peran pendidikan kewarganegaraan dalam menciptakan masyarakat yang harmonis di negara multietnik, yaitu di Malaysia dan Singapura. Malaysia dan Singapura adalah dua negara yang sama-sama bekas jajahan Inggris, dan dalam populasinya terdapat tiga etnis utama yaitu China, Melayu dan India. Tulisan ini merupakan studi literatur dengan menggunakan metode komparasi dengan menganalisis 14 jurnal nasional dan internasional terkait pendidikan kewarganegaraan dan keberagaman di Malaysia dan Singapura. Dari hasil penelitian dapat diketahui bahwa terdapat perbedaan dalam pengelolaan keberagaman etnis di Malaysia dan Singapura. Namun demikian baik di Malaysia maupun di Singapura, Pendidikan Kewarganegaraan sama-sama memegang peranan penting dalam menciptakan masyarakat yang harmonis walau dalam keberagaman budaya, bahasa, agama dan adat istiadat. Kata Kunci: Pendidikan Kewarganegaraan, multietnik, multikultural, Malaysia, Singapura